Isolasi Senyawa Aktif dari Ekstrak Hipokotil Sarang Semut (Myrmecodia pendens Merr. & Perry) sebagai Penghambat Xantinoksidase - PARTOMUAN SIMANJUNTAK; FANNY FANNY; MUHAMMAD AHKAM SUBROTO (Fakultas Farmasi Universitas Pancasila, 2010)
Medicinal plant called “sarang semut”, Myrmecodia pendens Merr. & Perry (Rubiaceae), is an epiphyt plant traditionally used in Papua for healing various diseases such as hyperuricemia, rheumatic, and cancer. A chemical compound recognized as xanthinoxidase inhibitor has been isolated from n-buthanol fraction of the plant extract. The isolation was carried out by column chromatography (SiO2, CHCI3-MeOH = 5:1-1:1) and the purification Was conducted using high pressure liquid chromatography (RP, C-18; MeOH-water = 5 : 1). The activity test for Xanthinoxidase inhibitor Was performmed by using modilied Noro method. The pure compound showed xanthinoxidase inhibitor activity of IC50 at 79,77%.